Emotions-at-risk: An experimental investigation into emotions, option prices and risk perception - Ronald Bosman; Roman Kräussl; Thomas van Galen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This paper experimentally investigates how emotions are associated with option prices and risk perception. Using a binary lottery, we find evidence that the emotion 'surprise' plays a significant role in the negative correlation between lottery returns and estimates of the price of a put option. Our findings shed new light on various existing theories on emotions and affect. We find gratitude, admiration, and joy to be positively associated with risk perception, although the affect heuristic predicts a negative association. In contrast with the predictions of the appraisal tendency framework (ATF), we document a negative correlation between option price and surprise for lottery winners. Finally, the results show that the option price is not associated with risk perception as commonly used in psychology.
urn:nbn:de:hebis:30:3-356099
Keywords: D81; D03; G17; 330; risk perception; emotions; affect heuristic; option prices; experiment